Evaluating health benefits of urban energy retrofitting: An application for the city of Turin. - Becchio, Cristina; Bottero, Marta C.; Corgnati, Stefano P.; Dell Anna, Federico (Springer, 2018)
The European Union (EU) has committed to lower greenhouse gas emissions for a 20 % with respect to 1990 by 2020, reaching an 80 % reduction by 2050. Renewable energy and buildings retrofitting will be key measures in cutting environmental impacts according to the new climate targets. The development of these energy-efficiency measures requires significant financial resources. The promotion of renewable-energy sources needs public acceptance to facilitate financial support for government. There is a growing body of literature that recognizes how the benefits of applying energy-efficiency measures outweigh the realization costs. Within this context, an evaluation of the whole range of co-impacts is crucial to compare different alternatives with the same objective. To implement a tool to assess the feasibility of a retrofitting project, firstly it is indispensable to identify the various possible benefits in a standardized manner and monetary terms. Secondly, it is fundamental to specify a logical path for assessing the attainment of these benefits, based on the features of the project. Recently, researchers have shown an increased interest in the evaluation of benefits. Despite this interest, very few studies have investigated the impact of the energy improvements of buildings on indoor comfort and human- health conditions. This work contributes to close the data gap in this context, investigating the health benefits connected to retrofitting interventions in residential buildings. A hybrid approach based on Contingent Valuation Method and economic analysis was applied to assess the impacts delivered by the energy retrofitting to an urban district in the city of Turin (Italy). A questionnaire was employed to elicit an estimate of consumers' Willingness-To-Pay for better indoor comfort conditions and fewer hazards to health, reducing poor building features in terms of energy efficiency and air quality. A bidding game model was created to converge to the expected annual economic value of acceptable comfort conditions in the residential houses.
Keywords: Klimawandel; Gesundheit; Energieeffizienz; Energetische Sanierung; Haus; Umbau